2014
DOI: 10.1038/srep04294
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-thick lateral polyelectrolyte micropatterns induce macrosopic electro-osmotic chaotic fluid instabilities

Abstract: Electro-convective vortices in ion concentration polarization under shear flow have been of practical relevance for desalination processes using electrodialysis. The phenomenon has been scientifically disregarded for decades, but is recently embraced by a growing fluid dynamics community due its complex superposition of multi-scale gradients in electrochemical potential and space charge interacting with emerging complex fluid momentum gradients. While the visualization, quantification and fundamental understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 23 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…Balster et al experimentally proved that chemical heterogeneity as well as micrometer‐sized geometrical embossed undulations, indeed, may impact on the evolution of electroconvection resulting in a decreased plateau length. Nanometer‐thick micrometer‐sized polyelectrolyte patterns transferred through microcontact printing on top of a membrane have the same effect on the emergence of electroosmotic induced fluid instabilities . Other works have shown that also hydrophobic surfaces lead to an intensified evolution of electroconvective vortices mixing the diffusion boundary layer .…”
Section: Introductionmentioning
confidence: 97%
“…Balster et al experimentally proved that chemical heterogeneity as well as micrometer‐sized geometrical embossed undulations, indeed, may impact on the evolution of electroconvection resulting in a decreased plateau length. Nanometer‐thick micrometer‐sized polyelectrolyte patterns transferred through microcontact printing on top of a membrane have the same effect on the emergence of electroosmotic induced fluid instabilities . Other works have shown that also hydrophobic surfaces lead to an intensified evolution of electroconvective vortices mixing the diffusion boundary layer .…”
Section: Introductionmentioning
confidence: 97%
“…In the electrochemical behavior of heterogeneous ion-exchange membranes, the electrical inhomogeneity of their surface, consisting ofthe presence of the regions with high (ion-exchanger phase) and low (polyethylene phase) conductivity, plays an important role. In [1][2][3][4][5][6][7][8][9][10], the possibility of mass transfer intensification in an electromembrane system by improving the morphology of the surface of ion-exchange membranes was demonstrated. The use of membranes with optimized surface morphology in the process of electrodialysis for desalting and deionization of natural waters and technological solutions creates the prerequisites for a significant increase in the efficiency of these processes in the limiting and overlimiting current modes.…”
Section: Introductionmentioning
confidence: 99%
“…Standard heterogeneous membranes display local limiting and overlimiting currents several times the average of homogeneous membranes, but with lower surface-averaged current densities 10 . However, recently, nanometer thick polyectrolyte layers deposited in micropatterns on ion exchange membranes were found to significantly shorten the limiting plateau length in the IV curve and increase OLC 11 . Thus, understanding the interactions between these two modes of electroconvection provides a promising avenue for designing surfaces that enhance OLC.…”
mentioning
confidence: 99%